Energy management scheduling for microgrids in the virtual power plant system using artificial neural networks - Abdolrasol M.G.M.; Hannan M.A.; Suhail Hussain S.M.; Ustun T.S.; Sarker M.R.; Ker P.J. (MDPI, 2023)
Controllers; Cost reduction; Electric load dispatching; Energy management; Microgrids; Neural networks; Control approach; Intelligent controllers; Microgrid; Multi micro-grids; Network-based; Performance; Power plant system; Scheduling control; System conditions; Virtual power plants; Scheduling